Merawat Damai Antar Umat Beragama Melalui Memori Kolektif dan Identitas Kultural Masyarakat Maluku - Lestari, Dewi Tika; Parihala, Yohanes (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2020)
This study aims to explain that the process of building and maintaining peace in the context of a plural society can be carried out by reactivating the collective memory and cultural identity of the community. Cultural memory and cultural identity that are based on historical-cultural experience are a social capital that nurtures harmony between communities. Qualitatively this study uses a literature study and field research approach. To explore the concepts of collective memory and cultural identity, author uses the concept from Edwards Shils, Maurice Halbwachs, and Paul Gilbert. The field study was obtained through a process of in-depth interviews with key informants, including religious leaders such as the Pastor and Imam of the Mosque, facilitators and community leaders in Batumerah from two communities, Islam and Christianity. Finally, the authors found that the collective memory of the cultural identity of Maluku people as brother people (orang basudara) is a strong social capital to transform conflict, and maintain peace among post-conflict communities. This can be a theoretical foothold in managing the diversity of peaceful lives as fellow brothers in Indonesia.